The required answer is StartFraction negative b plus or minus StartRoot b squared minus 4 a c EndRoot Over 2 a EndFraction, which is
![x = ((-1 +- √(5) ))/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vy1wa8gimsnl4jggjoh1lpd8g0idpila7j.png)
The quadratic equation's general structure is ax² + bx + c = 0 Here the given equation is 4x² + 2x - 1 = 0
These equations can be compared to see that a = 4, b = 2, c = -1
Typically, one uses the following equations to get the roots of a quadratic equation:
![x = (-b +- √(b^2 -4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p6bzpe09ugl9icif1kx4ytumlvgf0tt4x1.png)
![x = (-2 +- √(2^2 -4 * 4 * (-1)) )/(2* 4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1fz6rcdgunajdb7bmt2pwdkgeibzx5r3pp.png)
![x = (-2 +- √(4+16) )/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l7q27aiycq5yndmhd9v9p5m9h8twwhih60.png)
![x = (-2 +- √(20) )/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fh8opd1fsrjgr0u3j87un29owdhygufhpx.png)
![x = (-2 +- 2√(5) )/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gft1e3oqjusqr9dg0rd0rfp89uiblb6yyg.png)
![x = (2(-1 +- √(5) ))/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q2ds5ovcdvj3gc82494bysc1hw1ivaqppf.png)
![x = ((-1 +- √(5) ))/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vy1wa8gimsnl4jggjoh1lpd8g0idpila7j.png)
Question:
Which shows the correct substitution of the values a, b, and c from the equation 0 = 4x^(2) + 2x - 1 into the quadratic formula?